Pathogenesis and Factors associated with Insulin Resistance (KYAMC Journal, 2017)
Insulin resistance has been the subject of much debate over the last two decades. Its pathophysiological basis, however, still remains to be clearly understood. Both genetic and environmental factors have been implicated in its pathogenesis. Mutation of genes encoding signal transduction molecules of insulin and acquired factors like aging, diets, physical activity, obesity and related molecular changes, dyslipidemia, hypertension and smoking were proposed by many groups. This review examined both acquired and genetic factors and discussed model of hormone-receptor-postreceptor interactions to explore the molecular basis of insulin resistance.KYAMC Journal Vol. 5, No.-2, Jan 2015, Page 527-532